Application of Artificial Neural Network in Electrical Power System - P. Palanichamy (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The artificial neural network used to detect the fault in electrical machines and can increase the function of new entry detection when compared to the conventional method. In proposed artificial neural network has increased the precision and stability of system performance. The time-area vibration signs of a pivoting machine with ordinary and flawed apparatuses are handled for highlight extraction. The separated elements from unique and preprocessed signs are utilized as contributions to both classifiers in view of ANNs and SVMs for two-class (typical or blame) acknowledgment. The quantity of hubs in the concealed layer, if there should be an occurrence of ANNs, and the extend basis work section parameter, in the event of SVMs, alongside the choice of information components are enhanced utilizing genetic algorithm (GAs).